Annual Report FY19 : Transforming Evidence into Better Outcomes - Independent Evaluation Group (World Bank, Washington, DC, 2021)
In a year marked by change throughout the institution, the Independent Evaluation Group’s commitment to rigorous analysis, innovative methodological approaches, and the sharing of knowledge and lessons remains its foundation. Though topics ranged from forced displacement to creating markets, the evaluations presented similar stories about what is and is not working at the World Bank Group, providing guidance on improving outcomes. Common themes included building resilience, monitoring who benefits, and increasing private sector engagement. A highlight of FY19 was the release of the World Bank Group Evaluation Principles, co-led by the IEG Methods Adviser in collaboration with IFC, MIGA, and the World Bank. The principles act to solidify a Bank Group evaluation approach based on the evaluation framework established in FY18. The document delineates core principles for evaluation and underlying principles for planning, conducting, and using evaluations at the Bank Group. In FY20, IEG will position itself to provide even greater impact by focusing on the development effectiveness questions that most concern the institution and its clients in terms of what is needed to influence country development outcomes and where the Bank Group can do more, differently, or better. IEG has aligned its work program with Bank Group strategic priorities, keeping in mind the Sustainable Development Goals, commitments made in the IBRD and IFC Capital Packages, and the themes of the IDA’s last two replenishments (IDA18 and 19).